Utilization Of Antenatal Care Services In Periurban Area Of East Delhi - Aggarwal O.P; Kumar Rakesh; Gupta Anita; Tiwari R.S (Wolters Kluwer Medknow Publications, 1997)
Research question: What are the health care facilities availed by the antenatal mothers in a rural community. Objective: To assess the utilization of ante-natal care services in periurban areas of East Delhi. Design: Cross- sectional study. Participants: Mothers of 276 live born children during 1991. Results: Three quarters of mothers were aged between 20-30 years. 75% of them went for registration at one of the medical care centers. Around 27.5% of the births were of first birth order and 46% of the total live births were of 3+-birth order. Every 7th child born in the study area belonged to 5+ birth order. Around 70% of the deliveries took place at homes and 81.9% of these home deliveries were conducted by village-untrained dais. Conclusion: Mothers who do not register at any of the medical care centers are mostly illiterate, coming from poorer strata of population, below 25 years of age and bearing 3 or more children. Most of these unregistered mothers did not receive iron and folic acid tablets and TT immunization and finally delivered at home by untrained dais.